Two Step Clustering for Identifying the Causes of Surrender/ Forfeiture and Switchover of Life Insurance Policy: A Data Mining Technique - Garg, Kanwal; Kumar, Dharnzinder; Garg, M. C. (Gyan Management Journal, 2009)
The premise of this paper is to identify llze reason for Lapses Like Jorjeiture, surrender and w1u-J1ouer if policies i11 life insurance. ec/or. A practical dataset comprising of 2 0 allributes was formulated and distributed , in tlte farm of queslio1111aire. Out of the 500 opinion poll distributed, tlie data of 397 respondenl.s was collected and maintained in statiflical soft.ware SPSS version 75. 0. The data so collected is passed through two-step cluster analysis which is the desaiptwe technique of data, miningfor discovering the meanmgful knowledge. 77ie Clusters were thoroughly measured by AJ.C or BIG criterion. The ruling of thir study confirmed that financial difficulty in paying the premium a111ou11t, concealment of lite facts, product goodwill a11d service satisfaction are the key reasons for forfeiture, swilchiug and surrender of life insurance policies. The work presented in this paper makes n. unique contribution not only for companies in Life insurance sector but it will also C11courage the participation of customers.